Neurobiological Aspects of Violent and Criminal Behaviour: Deficit sin Frontal Lobe Function and Neurotransmitters (Academic Journal of Internal Affairs, 2023)
Aim: This review draws attention to the close interplay between violent criminal behaviour and brain, hormonal functions.Methodology: The presentation of the article is based on the methodology of content analysis and a professional breakdown following the structure of the article.Findings: The authors have undertaken a medical-biological approach to the study of aggression, presenting the prominent roles of the frontal lobe of the brain and of neurotransmitters and hormones in the manifestation of violent behaviour.Value: The study interprets the possible neurobiological reasons behind violent behaviour in a way that is understandable to readers less familiar with science and medicine.
Keywords: criminal behavior; neurobiology; review